ANALISA PENGARUH PENAMBAHAN UNSUR Cu DAN VARIASI TEMPERATUR PELEBURAN TERHADAP SIFAT MEKANIK KEPALA PISTON - Achmad, Zainun; Setiawan, Sony (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2017)
This study aims to determine the effect of adding Cu elements and variations in meltingtemperature to mechanical properties on the piston head.From this research used as main material that is used piston head melted into furnace withvariation of melting temperature such as 680 oC, 700 oC, and 720 oC and will be combinedwith Cu alloy with variation of 2%, 4%, and 6%. There will be further impact testing andmicrostructure testing.From the research, it can be concluded that on impact test at 680 oC, 700 oC, and 720 oCmelting temperature and addition of Cu 2%, 4%, and 6%. Experiencing increased energyabsorbed and impact price of raw material. While at 720â°C temperature combined with Cu6% of energy absorbed by 2.28 joules and for the impact price is 0.036 Joule / mm2. Moreresilient than other material impact prices. Each addition of melting temperature andaddition of Cu elements produce impact and energy values absorbed differently. And themore the impact price is high, the fracture of the specimen becomes resilient as well as viceversa, if the impact price is low the fracture of the specimen becomes brittle. As for theresults of microstructure testing performed, each addition of Cu elements and meltingtemperature resulted in different microstructures and each addition of Cu elements willproduce a new phase that is CuAl2 which in this phase can cause the material becomestougher than raw material.